METHYL ESTER EXTRACTION OF SUNFLOWER OIL IN A TWIN SCREW EXTRUDER - Ika Amalia Kartika (Jurnal Teknologi Industri Pertanian, 2008)
ABSTRACTSunflower oil was extracted from whole sunflower seeds using methyl ester as the solvent. Experiments were conducted in a co-rotating twin-screw extruder. The oil extraction yield was measured as function of screw configuration and solvent-to-solid (S/S) ratio. The position of the reverse screw elements affected oil extraction yield. Higher oil recovery was produced as the S/S ratio was increased. Up to 90% of the oil was removed from seeds under S/S ratio of 0.65. The methyl ester is thus a promising alternative solvent for extraction of sunflower oil.   Keywords : twin-screw extruder,  sunflower oil,  methyl ester and extraction